Collaborative Inquiry Groups: Empowering Teachers to Work with English Language Learners - Kevin Murry; Socorro Herrera (Journal of Teaching and Learning, 2010)
As grade-level teachers in the United States become increasingly responsible for educating English language learning (ELL) students, it is imperative that they re-evaluate their perspectives on instruction. This paper describes a program designed to prepare in-service teachers for enhancing their instructional effectiveness with ELL students in their traditional classrooms. The program emphasizes the use of collaborative inquiry groups in which teachers serve as critical colleagues, challenging one another to implement research and theory-driven practices and, most importantly, reflect upon their existing assumptions with regard to the instruction of ELL students. Teachers participating in the program completed a survey to describe their experience in an inquiry group. The findings of this study demonstrate noteworthy changes in teacher perspectives on language differences among, and appropriate literacy paradigms for, ELL students. Key among these changes were participants’ demonstrated transformations in perspective regarding the role of native language support in ELL students’ development of literacy and content-area skills and understandings.